Distribution of methane-cycling archaea in buried ridge flank sediment: community zonation, activity, and potential environmental drivers - Lever, Mark Alexander; Morono, Yuki; Inagaki, Fumio; Teske, Andreas P. (Frontiers in Microbiology, 2025)
Subseafloor sediments harbor Earth’s biggest reservoir of methane, with most of this methane being produced biologically by methanogenic archaea (methanogens). Yet, little is known about the controls on in situ abundances, community structure, and biochemical pathways of methanogens, and closely related anaerobic methane oxidizing archaea (ANMEs), in these environments. Here we examine the vertical distribution of methane-cycling archaea at Integrated Ocean Drilling Program Site U1301, an offshore drilling site on the eastern flank of the Juan de Fuca Ridge, that was previously characterized with respect to its in situ temperature profile, sediment provenance, geochemical gradients, and general microbial community structure. We integrate (1) functional gene analyses (mcrA) to analyze methane-cycling archaeal abundances and community structure with (2) sediment porewater concentration profiles of sulfate, methane, Mn2+, and Fe2+ to shed light on the distributions of dominant microorganisms and processes involved in subseafloor methane cycling. These analyses indicate that sediments from the cold seafloor (2 °C) to the hot basement (64 °C), across zones of sulfate reduction (SR), anaerobic oxidation of methane (AOM), and methanogenesis (MG), were dominated by two phylogenetic clusters. These belonged to the family Methanoperedenaceae, which couples the oxidation of methane to the reduction of nitrate or metals, and the candidate order Methanophagales (group ANME-1a-b). The latter has mainly been linked to sulfate-dependent AOM, although a facultative methanogenic metabolism has also been proposed. Other groups of methane-cycling archaea (ANME-2c, -3, Methanothrix, Methanocellales, Candidatus Nezhaarchaeales) were only detected in single samples from the upper and lower AOM zones and the MG zone. No stimulation of methanogenic activity was evident at the deep sediment-basement interface; however, the dominant Methanoperedenaceae and Methanophagales phylotypes throughout the sediment column cluster phylogenetically with those previously detected in underlying basalt, suggesting dispersal and similar selective forces on methane-cycling archaea across this major lithological boundary. Based on the observed dominance of Methanoperedenaceae and porewater geochemical profiles which indicate decoupling between measured sulfate and methane concentrations in sediments with methane oxidation, we propose that a significant portion of AOM in the iron- and manganese-rich sediments of the Juan de Fuca Ridge Flank proceeds through the reduction of iron (III) and manganese (IV).